Palaeoproterozoic terrane assembly in the Lewisian Gneiss Complex on the Scottish mainland, south of Gruinard Bay: SHRIMP U–Pb zircon evidence - Love, Gary; Friend, C.; Kinny, Peter (Elsevier Science BV, 2010)
New SHRIMP U–Pb zircon geochronology and fieldwork integrated with reappraisal of earlier mapping demonstrates that the so-called ‘southern region’ of the mainland Lewisian Gneiss Complex comprises a package of distinct tectono-stratigraphic units. From south to north these are the Rona (3135–2889 Ma), Ialltaig (c. 2000 Ma) and Gairloch (ca. 2200 Ma) terranes. These terranes were metamorphosed and deformed separately until ca. 1670 Ma by which time they had been juxtaposed and were integral with terranes to the north. The northern boundary of the Palaeoproterozoic Gairloch terrane is a shear zone, north of which is the Archaean Gruinard terrane with 2860–2800 Ma protoliths and ca. 2730 Ma granulite facies metamorphism. In contrast, south of the Gairloch terrane, the Archaean gneisses of the Rona terrane have older protolith ages, underwent an anatectic event at ca. 2950 Ma and show no evidence of 2730 Ma granulite facies metamorphism. In current structural interpretations the Gruinard terrane forms a structural klippe over the intervening Gairloch terrane.However, the Rona and Gruinard terranes cannot be equivalent on age grounds, and are interpreted as unrelated different entities. Contained within the southern margin of the Gairloch terrane is the Ialltaig terrane, shown here to comprise an exotic slice of granulite facies Palaeoproterozoic crust, rather than Archaean basement as previously thought. The ca. 1877 Ma granulite facies metamorphism of the Ialltaig terrane is the youngest event that is unique to a single terrane in the mainland Complex, making it an upper estimate for the timing of amalgamation with surrounding tectonic units. U–Pb titanite ages of 1670 ± 12 Ma and ca. 1660 Ma for low-strain zones at Diabaig are interpreted to be cooling through the titanite closure temperature after the amphibolite facies reworking of these southern terranes and the southern margin of the Gruinard Terrane. These new data have implications for the tectonic setting of the mainland in relation to the Outer Hebrides and in the wider evolution of the basement in the North Atlantic.